2019
DOI: 10.1002/jcp.28889
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals lncRNA‐mediated complex regulatory network response to DNA damage in the liver tissue of Rattus norvegicus

Abstract: DNA is prone to damages, which would result in genetic disorders and enhance risk of tumorigenesis. Hence, understanding the molecular mechanisms of DNA damage and repair will provide deep insights into tumorigenesis, carcinogenesis as well as the corresponding treatments. Aiming at investigating potential long noncoding RNAs (lncRNAs) response against DNA damage, we performed a comprehensive transcriptomic analysis based on RNA sequencing data of the liver tissue from Rattus norvegicus, in which DNA damage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Despite the function of majority of lncRNAs are unknown so far, their important roles in diverse biological processes has already been demonstrated, particularly close correlations to diseases. In the present study, we detected at least one order of magnitude lncRNAs larger than those identified in our previous studies about lncRNAs [ 38 , 42 , 43 ]. One of reason is the strategy of RNA sequencing in our previous studies is to capture the RNAs with polyA tail (mRNAs), which could only identify around half of lncRNAs.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Despite the function of majority of lncRNAs are unknown so far, their important roles in diverse biological processes has already been demonstrated, particularly close correlations to diseases. In the present study, we detected at least one order of magnitude lncRNAs larger than those identified in our previous studies about lncRNAs [ 38 , 42 , 43 ]. One of reason is the strategy of RNA sequencing in our previous studies is to capture the RNAs with polyA tail (mRNAs), which could only identify around half of lncRNAs.…”
Section: Discussionsupporting
confidence: 45%
“…Subsequent network analysis based on PCC method displayed that GUSBP2 might target on KLRK1, whose expression was also already found to be up-regulated after desensitization treatment. Notably, the cutoff of correlation value was not set to traditional threshold (0.9 ~ 0.95) since the correlation between those transcripts in this study is not as strong as our previous lncRNA studies [ 38 , 43 ]. One of possible reason is that the desensitization treatment might not make a big change of RNAs in peripheral blood of these asthmatics, which further led to weak correlations among those RNAs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite the function of majority of lncRNAs are unknown so far, their important roles in diverse biological processes has already been demonstrated, particularly close correlations to diseases. In the present study, we detected at least one order of magnitude lncRNAs larger than those identified in our previous studies about lncRNAs [43][44][45]. One of reason is the strategy of RNA sequencing in our previous studies is to capture the RNAs with polyA tail (mRNAs), which could only identify around half of lncRNAs.…”
Section: Discussionmentioning
confidence: 49%
“…Notably, the cutoff of correlation value was not set to traditional threshold (0.9~0.95) since the correlation between those transcripts in this study is not as strong as our previous lncRNA studies [44,45]. One of possible reason is that the desensitization treatment might not make a big change of RNAs in peripheral blood of these asthmatics, which further led to weak correlations among those RNAs.…”
Section: Discussionmentioning
confidence: 75%